Fiscal instruments supporting families in Poland in the years 2004-2017 - Michał Wojciuk; Łukasz Zegarowicz (e-Finanse: Financial Internet Quarterly, 2019)
The main objective of the study was an attempt to describe the policy for supporting families with children in Poland in the years 2004-2017 in the context of traditional support instruments. The following research methods were used in the article: analysis of the literature on the subject and legal acts, analysis of statistical data and comparative analysis. The study uses statistical data from reports of the Ministry of Finance and the Ministry of Family, Labor and Social Policy. The study did not confirm the research hypothesis which says that in the analyzed period, tax preferences were the dominant instrument of support for families in Poland. Shifting the burden of family policy towards direct benefits is unlikely to increase the transparency of this policy. With the introduction of new family benefits at a high level, which are the subject of exemption from personal income tax, public spending made with the use of tax expenditures will also increase. The lack of detailed and cyclical reporting of this type of expenditure in Poland reduces the transparency of the family policy.
Keywords: H53; J13; H24; 330; family policy; fiscal policy; tax expenditures; tax preferences; family benefit